Neoglycoconjugate of Tetrasaccharide Representing One Repeating Unit of the Streptococcus pneumoniae Type 14 Capsular Polysaccharide Induces the Production of Opsonizing IgG1 Antibodies and Possesses the Highest Protective Activity As Compared to Hexa- and Octasaccharide Conjugates - Kurbatova, Ekaterina A.; Akhmatova, Nelli K.; Akhmatova, Elina A.; Egorova, Nadezhda B.; Yastrebova, Natalya E.; Sukhova, Elena V.; Yashunsky, Dmitriy V.; Tsvetkov, Yury E.; Gening, Marina L.; Nifantiev, Nikolay E. (Frontiers in Immunology, 2017)
Identifying protective synthetic oligosaccharide (OS) epitopes of Streptococcus pneumoniae capsular polysaccharides (CP) is an indispensable step in the development of third generation carbohydrate pneumococcal vaccines. Synthetic tetra-, hexa-, and octasaccharide structurally related to CP of S. pneumoniae Type 14 were coupled to BSA, adjuvanted with aluminum hydroxide and tested for their immunogenicity in mice upon intraperitoneal prime-boost immunizations. Injections of the conjugates induced production of opsonizing anti-OS IgG1 antibodies. Immunization with the tetra- and octasaccharide conjugates stimulated the highest titers of the specific antibodies. Further, the tetrasaccharide ligand demonstrated the highest ability to bind OS and CP antibodies. Murine immune sera developed against tetra- and octasaccharide conjugates promoted pathogen opsonization to a higher degree than antisera against conjugated hexasaccharide. For the first time, the protective activities of these glycoconjugates were demonstrated in mouse model of generalized pneumococcal infections. The tetrasaccharide conjugate possessed the highest protective activities. Conversely, the octasaccharide conjugate had lower protective activities and the lowest one showed the hexasaccharide conjugate. Sera against all of the glycoconjugates passively protected naive mice from pneumococcal infections. Given that the BSA-tetrasaccharide induced the most abundant yield of specific antibodies and the best protective activity, this OS may be regarded as the most promising candidate for the development of conjugated vaccines against S. pneumoniae type 14 infections.